2022
DOI: 10.1016/j.ekir.2022.01.1056
|View full text |Cite
|
Sign up to set email alerts
|

Acetate-Free Biofiltration Versus Online Acetate-Free Hemodiafiltration in Patients at High Risk of Hemodialysis Intolerance

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…36 Apter et al recently showed that the incidence of intradialytic hypotension in patients at high risk of hemodialysis intolerance is lower during AFB than during acetate-free hemodiafiltration, suggesting that some of the benefits of AFB are related to its acid-free rather than acetate-free nature. 37 During regional anticoagulation with calcium-free dialysate, acidification of the dialysate is also not necessary because calcium and bicarbonate are not present simultaneously in the dialysate, as in AFB and DCB. This acidification can be avoided by substituting trisodium citrate for citric acid in the concentrate used to supply the dialysate.…”
Section: Heparin-and Acid -Free Routine Hemodialysismentioning
confidence: 99%
See 1 more Smart Citation
“…36 Apter et al recently showed that the incidence of intradialytic hypotension in patients at high risk of hemodialysis intolerance is lower during AFB than during acetate-free hemodiafiltration, suggesting that some of the benefits of AFB are related to its acid-free rather than acetate-free nature. 37 During regional anticoagulation with calcium-free dialysate, acidification of the dialysate is also not necessary because calcium and bicarbonate are not present simultaneously in the dialysate, as in AFB and DCB. This acidification can be avoided by substituting trisodium citrate for citric acid in the concentrate used to supply the dialysate.…”
Section: Heparin-and Acid -Free Routine Hemodialysismentioning
confidence: 99%
“…Apter et al. recently showed that the incidence of intradialytic hypotension in patients at high risk of hemodialysis intolerance is lower during AFB than during acetate‐free hemodiafiltration, suggesting that some of the benefits of AFB are related to its acid‐free rather than acetate‐free nature 37 …”
Section: Toward Heparin‐ and Acid‐free Routine Hemodialysismentioning
confidence: 99%
“…Citrate-based treatments, despite being acetate-free, show increased partial pressure of CO 2 in blood exiting the extracorporeal circuit and are associated with hemodynamic instability [7]. Cardiac output and peripheral vascular resistance do not change by replacing acetic with citric acid [8], but a significant decrease in IH incidence occurs if acid is removed by dialysate: patients receiving HDF with acetate-free chloride-based dialysate improved their hemodynamic stability during 3-month period of AFB [9]. Taken all together, these evidence suggest that hemodynamic tolerance is not related to acetate anion but to the lack of acid, regardless of what it is.…”
mentioning
confidence: 99%